2009
DOI: 10.1039/b822337h
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented double migratory insertion of phenyl isocyanide into cyclopentadienyl C–H bonds

Abstract: The reaction of [(eta(5)-C(5)H(5))Cu(CNPh)] with phenyl-isocyanide results in an unprecedented double migratory insertion into two sp(2) C-H bonds of a eta(5)-coordinated cyclopentadienyl group, and formation of the 6-aminofulvene-2-aldimine complexes [(CNPh)Cu{kappa(2)-N,N-C(5)H(3)-1,2-(CHNPh)(2)}] and [(CNPh)(2)Cu{kappa(2)-N,N-C(5)H(3)-1,2-(CHNPh)(2)}], respectively, both of which have been structurally characterised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The bond lengths within the cyclopentadienyl ring vary only to a small degree (max deviation of 0.012 Å in the case of 4a ·(CS 2 ) 3 ) and the pyramidalization angles of the carbon atoms of the cyclopentadienyl ring are nearly equal. These variations in bond lengths and angles are comparable to those of pentahapto “buckyferrocenes”, e.g., (η 5 -C 60 Me 5 )FeCp, and also to those of other copper(I) cyclopentadienyl phosphine complexes …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bond lengths within the cyclopentadienyl ring vary only to a small degree (max deviation of 0.012 Å in the case of 4a ·(CS 2 ) 3 ) and the pyramidalization angles of the carbon atoms of the cyclopentadienyl ring are nearly equal. These variations in bond lengths and angles are comparable to those of pentahapto “buckyferrocenes”, e.g., (η 5 -C 60 Me 5 )FeCp, and also to those of other copper(I) cyclopentadienyl phosphine complexes …”
Section: Resultsmentioning
confidence: 99%
“…Cyclopentadienyl complexes of the coinage metals are dramatically underrepresented in comparison to those of earlier transition metals. Although only a handful of group 11 metal cyclopentadienyl complexes have been isolated and characterized crystallographically, a range of coordination modes between the cyclopentadienyl ligand and the metal center has nonetheless been observed. , The characterization of group 11 metal cyclopentadienyl compounds, especially of copper and silver, has often been hampered by their instability and high sensitivity to air. These issues have been addressed in some instances by using bulky phosphine or cyclopentadienyl ligands.…”
Section: Introductionmentioning
confidence: 99%
“…As part of a wider study into the coordination chemistry of Cu I complexes, we have recently reported the double migratory insertion of phenyl isocyanide (Ph-NC) into two vicinal sp 2 C-H bonds of the 5 -coordinated cyclopentadienyl group in the complex [( 5 -C 5 H 5 )Cu(CNPh)], resulting in the formation and isolation of the AFA complexes [(Ph 2 -AFA)Cu(CNPh)] and [(Ph 2 -AFA)Cu(CNPh) 2 ] (Johnson et al, 2009).…”
Section: Commentmentioning
confidence: 99%
“…The reaction of both [( 5 -C 5 H 5 )Cu(CN t Bu)] and [( 5 -C 5 H 5 )Cu(CNPh)] with an excess of the alkyl isocyanide, CN t Bu (ca 4 equivalents) was studied, but 1 H NMR spectroscopic studies failed to establish any evidence of reaction. However, the analogous reaction of [( 5 -C 5 H 5 )Cu(CN t Bu)] (Kruck et al, 1993) with an excess (4 equivalents) of CNPh has been shown to produce the AFA complex, [(Ph 2 -AFA)Cu(CNPh) 2 ], as evidenced by the appearance of indicative resonances for the ligand system in the 1 H NMR spectra, and provides an alternative route for the synthesis of the complex (Johnson et al, 2009). We previously noted that the reaction of [( 5 -C 5 H 5 )Cu(CN t Bu)] with the electron-withdrawing isocyanides CN(p-C 6 H 4 F) and CN(p-C 6 H 4 NO 2 ) shows a much more rapid production of AFA complexes (<< 12 h), indicating that the electronic nature of the isocyanide is a significant factor in the migratory insertion of isocyanides into C-H bonds of the Cu-C 5 H 5 systems (Johnson et al, 2009).…”
Section: Commentmentioning
confidence: 99%
“…[7][8][9] Even double insertion into two C-H bonds of a h 5 -coordinated cyclopentadienyl group at Cu(I) leading to an 6-aminofulvene-2-aldimine complex has been reported. 10 In contrast, MI of CO into metal acyl bonds has only rarely been reported and considered thermodynamically unfavorable, which is fundamental for the chemoselectivity of hydroformylation. 11,12 The reactivity of related formyl complexes is governed by the high stability of either metal hydride (reverse MI) or the CO complex (hydride transfer).…”
Section: Introductionmentioning
confidence: 99%